Baling Malay: A Preliminary Description: (Dialek Melayu Baling: Satu Pemerian Awal) (Jurnal Bahasa, 2021)
It is proven that dialects in the rural areas have different linguistic systems compared to urban areas. One of the dialects in the rural area considered to be distinctive among Malay dialects us that found in the district of Baling in Kedah. This study aims to examine the phonological system of the Baling Malay dialect. The analysis focuses on the distribution of vocal phonemes and several phonological features that illustrate the dialect's distinctiveness. Phoneme characterization is performed based on the method proposed in Basic Linguistic Theory, while the analysis of phonological features is carried out by applying a diachronic dialectology framework that focuses on representation, comparison and clustering. The existence of consonants [ɣ] and phonological processes such as the nasal unification of BMP *-am to [-an], the unification of the diphthongs of BMP *-aw and *-ay to [ɔ], besides the retention of BMP *ɣ at the beginning and between vowels and its deletion at the end that change the preceding vowel clearly show that the Malay dialect of Baling differs from the assumptions of previous researchers. This means that Baling Malay is a dialect in its own right rather than merely being a subdialect of Kedah Malay, and should be considered as requiring its own clustering and nomenclature. The implication of this discovery is that it renders inaccurate the general perception that Malay dialects within one state on the Peninsula are "subdialects" of the Malay spoken in that state.